Boron-Doped Anatase TiO2 as a High-Performance Anode Material for Sodium-Ion Batteries - Wang, Baofeng; Zhao, Fei; Du, Guodong; Porter, Spencer; Liu, Yong; Zhang, Peng; Cheng, Zhenxiang; Liu, Hua Kun; Huang, Zhenguo (ACS applied materials & interfaces, 2016)
Pristine and boron-doped anatase TiO2 were prepared via a facile sol–gel method and the hydrothermal method for application as anode materials in sodium-ion batteries (SIBs). The sol–gel method leads to agglomerated TiO2, whereas the hydrothermal method is conducive to the formation of highly crystalline and discrete nanoparticles. The structure, morphology, and electrochemical properties were studied. The crystal size of TiO2 with boron doping is smaller than that of the nondoped crystals, which indicates that the addition of boron can inhibit the crystal growth. The electrochemical measurements demonstrated that the reversible capacity of the B-doped TiO2 is higher than that for the pristine sample. B-doping also effectively enhances the rate performance. The capacity of the B-doped TiO2 could reach 150 mAh/g at the high current rate of 2C and the capacity decay is only about 8 mAh/g over 400 cycles. The remarkable performance could be attributed to the lattice expansion resulting from B doping and the shortened Li+ diffusion distance due to the nanosize. These results indicate that B-doped TiO2 can be a good candidate for SIBs.